CODE-SWITCHING IN WHATSAPP GROUP: A SOCIAL REALTY AMID COVID-19 PANDEMIC - Endang Yuliani Rahayu; Agnes Widyaningrum; Yulistiyanti Yulistiyanti; Teguh Kasprabowo (PRASASTI: Journal of Linguistics, 2021)
The current study examined the use of Code-Switching in WhatsApp Group (WAG) to find out what codes were used and switched among users of WA and in particular to identify the rationales for such a discursive practice in their communication amid Covid-19 Pandemic. Data for this study were screenshots of linguistic exchanges in WAG over a period of two days (weekend). Theoretical  framework  for  the  use  of Code- Switching was highlighted as the basis of data analysis. Findings reveal  that most members of WAG employ intrasentential code-switching.  Regarding the rationales of code-switching, most members used code- switching to talk about particular topics and to show emphaty. The study concludes that code switching is a social reality in a multilingual and multicultural society of diverse educational background. It is highly recommended that similar studies be conducted in some wider and more diverse strata of people in the use of CS to support a newly coined term ‘Permanent Code Switching’ (PCS).